Soil Carbon and Nitrogen Transformations under Soybean as Influenced by Organic Farming. (1st September 2018) - Tian, X.M.; Fan, H.; Zhang, F.H.; Wang, K.Y.; Ippolito, J.A.; Li, J.H.; Jiao, Z.W.; Li, Y.B.; Li, Y.Y.; Su, J.X.; Li, W.T.; An, M.J.
Abstract : Organic farming significantly increased or improved many soil properties, including the mean weight diameter of aggregates, soil organic matter, available N, soil microbial diversity, and soil C and N transformation rates. Soybean yield was also 13.7 % greater in the organic farming treatment than in conventional farming treatment. Organic farming increased soil Cu and Ni; however, their concentrations were still less than the allowable limits for organic production. Organic farming with composted manure application improved soil properties and altered the structure and function of the microbial community. The <0.25‐mm aggregate fraction had a major influence on microbially mediated C and N transformations and soybean yield. Organic farmers use natural inputs and ecological principles to produce crops in ways that protect soil, the environment, and human health. The objectives of this study were to determine (i) how organic farming with composted manure application affects soil properties under soybean and (ii) how soil C and N transformations in this system are related to soil microbial community structure, soil nutrient and heavy metal content, and soybean yield and quality. The results showed that three years of organic farming promoted soil aggregation and significantly increased aggregate associated C and N concentrations by 11.7 to 24.1% and 9.4 to 17.0%, respectively. Microbial biomass and species diversity (i.e., Shannon, Simpson, and Pielou indexes) were significantly greater in the organic farming than in the conventional farming. Organic farming also increased soil respiration by 56%, nitrification by 51%, and dentrification by 75%. Soybean yield was 13.7% in the organic farming than in conventional farming. Organic farming increased soil Cu and Ni; however, their concentrations were still less than the allowable limits for organic production. Redundancy analysis indicated that the increases in soil nutrient content, heavy metal content, and soybean yield in the organic farming were closely linked with C and N concentrations in the <0.25‐mm size fraction. In summary, organic farming with composted manure application improved soil properties and altered the structure and function of the microbial community. The <0.25‐mm aggregate fraction had a major influence on microbially mediated C and N transformations and soybean yield.